2013
DOI: 10.1103/physrevb.87.045421
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption height determination of nonequivalent C and O species of PTCDA on Ag(110) using x-ray standing waves

Abstract: The normal incidence x-ray standing wave (NIXSW) technique is used to determine the adsorption geometry of submonolayer 3,4,9,10-perylene tetracarboxylic dianhydride (PTCDA) adsorbed on the Ag (110) surface. An accurate analysis of both C1s and O1s photoemission (PE) spectra allows the respective adsorption heights of carbon and oxygen atoms in different chemical environments within PTCDA to be distinguished. Due to the intricacy of the PE fitting models, a systematic error analysis of NIXSW structural paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 52 publications
8
77
1
Order By: Relevance
“…This causes an "M-like" distortion of the molecules (both oxygen species lie underneath the carbon backbone), in contrast to the typical saddle-like geometry found for PTCDA/Ag(1 1 1) [16] and for the MBW structure. Such a geometry was already reported for PTCDA adsorbed on more reactive surfaces like Ag(1 0 0) and Ag(1 1 0) [47,68] and can be explained by an enhanced interaction between the anhydride oxygen atoms and the silver surface, enhanced with respect to the carboxylic oxygen atoms. It was also reported that for the homomolecular systems the transformation to the M-shape goes along with a LUMO downshift (toward higher binding energies) and hence is an indication for an enhanced electronic interaction between molecule and surface.…”
Section: Vertical Structurementioning
confidence: 67%
“…This causes an "M-like" distortion of the molecules (both oxygen species lie underneath the carbon backbone), in contrast to the typical saddle-like geometry found for PTCDA/Ag(1 1 1) [16] and for the MBW structure. Such a geometry was already reported for PTCDA adsorbed on more reactive surfaces like Ag(1 0 0) and Ag(1 1 0) [47,68] and can be explained by an enhanced interaction between the anhydride oxygen atoms and the silver surface, enhanced with respect to the carboxylic oxygen atoms. It was also reported that for the homomolecular systems the transformation to the M-shape goes along with a LUMO downshift (toward higher binding energies) and hence is an indication for an enhanced electronic interaction between molecule and surface.…”
Section: Vertical Structurementioning
confidence: 67%
“…In contrast, PTCDA is significantly distorted, similar to the case of the PTCDA monolayer structure on Ag(111): The carboxylic oxygen atoms approach the silver surface while the anhydride oxygen atoms are shifted to a position above the molecular backbone. This finding, and the overall adsorption height of PTCDA, indicates a chemical interaction between the molecule and the silver surface as it is known from the homomolecular adsorbate structure [11,43,44,46]. However, in the bilayer structure the vertical distance between both oxygen species is reduced by a factor of 2 compared to the PTCDA monolayer film, i.e., the bending of the molecule is reduced by the on-top adsorption of CuPc.…”
Section: -7mentioning
confidence: 75%
“…The two peaks are attributed to two chemically different oxygen species in the PTCDA molecule, the carboxylic and the anhydride oxygen atoms (with smaller and larger binding energy, respectively). The fact that the two peaks do not reflect the stoichiometric ratio 2 : 1 and the shoulder on the high binding energy side of the spectra indicate that both peaks have (rather complex) satellite structures [42][43][44]. The corresponding fitting model is shown in Fig.…”
Section: Core-level Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, experimental studies on the molecule-substrate bonding distances, which provide the points of reference for adequate theoretical modeling, are rare-in contrast to the numerous experimental studies on single molecule adsorption [15,16] and 2D molecular layers based on intermolecular interactions different than metal coordination [17][18][19][20][21][22][23][24][25][26]. However, these data are crucial for understanding molecule-substrate interactions and of interest for determining possible distortions from the planar geometry of surface-confined 2D MOFs.…”
Section: Introductionmentioning
confidence: 99%